History of the Book in Canada: The View from Here - Gerson, Carole (Mémoires du livre / Studies in Book Culture)

(untitled) (Groupe de recherches et d’études sur le livre au Québec, 2016)
National book history projects are both informative and provocative: informative for the resources they assemble and the knowledge they promote, and provocative for their omissions and limitations. The History of the Book in Canada/Histoire du livre et de l’imprimé au Canada (3 vols 2004-2007) provided a remarkable opportunity for a large community of researchers across the country to investigate myriad aspects of Canada’s print culture in an increasingly multicultural population. Their focal points included authorship, publishing, distribution, and reading. The project established a baseline for subsequent studies in areas that were revealed to be under-researched and it continues to inspire new scholarly investigations. Working in both official languages, HBiC/HLIC’s editorial team forged a model for bilingual scholarly dissemination, a format that is surprisingly rare in the humanities in Canada. At the national level, its three volumes and many offshoots have enriched Canadians’ knowledge about themselves; at the international level, the project has established the presence of a relatively small country within the realm of global book history. As international book history scholars become increasingly conscious of the need to situate their investigations within trans-national contexts, we invite them to consider Canada’s stories and examples.